The Changed and Unchanged Situations in the Representation of Women in Contemporary Cinema - Arif Rohman (Humaniora, 2013)
The second feminist wave in the 1960s has influenced feminists to increase their campaign against patriarchy in almost all areas. One of the areas which has made women very vulnerable is the issue of women in cinema. This article investigates some changes in the representation of women in cinema by comparing four movies: Stepford Wives (1975), Orlando (1992), When Night Is Falling (1995), and Stepford Wives (2004). This study was conducted by using modern hermeneutics method. The results indicate that these four films appear to contain three changed aspects regarding women, that is, the equality of work, the expression of sexual identity, and the image of ‘higher-education-woman’. The films also show that some aspects in the representation of women, such as the expectation of motherhood, the myth of sexuality, and the position of women as victims, remain unchanged.